Störs laxens lekvandring i en kraftverkspåverkad älvsträcka? - Lundgren, Johan (SLU/Dept. Of Aquatic Resources, 2006)
The upstream spawning migration of Atlantic salmon (Salmo salar) at the confluence area between the power-station outlet and the bypass-channel in river Umeälven (flow 430 m3s-1) was compared in 2004 and 2005, two years with different experimental flow-regimes. In 2004 the water flow in the bypass-channel was altered during the day with increased flows during the nights while the water flow in 2005 mainly was altered between the weekdays and weekends. Salmon showed altered migratory behaviour in this confluence area, assessed with telemetry (n=116) and echo-sounding, with up- or downstream responses depending on flow-changes in both the bypass and the power station outlet. Increased turbine flow through the power-station generally attracted salmon into the tunnel outlet area while increased spill-flows facilitated salmon to enter the bypass. Echo-sounding in the confluence area showed an increased swimming activity up- and downstream due to time in the day and flow-rates through the tunnel outlet. No changes in activity could be detected due to increasing or decreasing flow through the hydro-power facility. About 70 % of the registrated movements originated from salmon swimming downstream and fish were found across the whole outlet channel and down to 40 m depth. In 2004 the spill-flows were regulated on daily basis and caused elevated movements of salmon and a prolonged stay of salmon at the confluence area compared to year 2005 with weekly spill-flow patterns. In addition, the migration success of salmon to the fish-ladder 32 km upstream the river mouth was lower (21 % vs. 44 %) and travel-time higher (42,6 day vs. 35,7 day) in 2004 than 2005, respectively. The overall results demonstrate the negative effects of rapidly changing flows on salmon upstream migration success. Beteendet hos lekvandrande lax (Salmo salar) i sammanflödesområdet i Umeälvens nedre del (medelflöde 430 m3s-1), mellan turbinutlopp och den flödesreglerade ”gamla älvfåran”, jämfördes för åren 2004 och 2005. Flödet i torrfåran har under ...